The fall of the house of Usher and other selected stories - Poe, Edgar Allan, 1809-1849 (Vintage American gothic., 2023)
Edgar Allan Poe was a writer of uncommon talent; in The Murders in the Rue Morgue he created the genre of detective fiction while his genius for finding the strangeness lurking within us all has been an influence on everyone from Freud to Hollywood. This complete collection of all his short stories and novellas contains well-known tales 'The Pit and the Pendulum' and 'The Tell-Tale Heart' alongside hidden gems that both unsettle and enthral the reader.